Closure - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Journal of Infrastructure & Facility Asset Management Volume 3, Issue 3, December 2021 (e) ISSN 2656-8896 (P) ISSN 2656-890X JIFAM, Vol.3, Issue 2, August 2021 Neighborhood for Adolescent Girls: The Case of Urban Dense Kampong In Yogyakarta City Center Mu’afifah & Setiawan Cengklik Reservoir Tourism Development with approach Eco-Waterfront Auliya Rohmah Ramadhani, Budi Prayitno & Wiwik Setyaningsih Early Chinese Settlements Adaptive Reuse as History and Activity Node at Lasem Living Museum Ardelia J. Cungwin & Widjaja Martokusumo Improvement Strategy for KOTAKU program in Slum Settlements Area in Sidoarjo Ririn Putri Kusuma & Dian Rahmawati Urban Resilience: How to Apply in the Planning and Design Practice? Novi Maulida Ni’mah & Bakti Setiawan JIFAM, Vol.3, Issue 1, March 2021 Framework for Facilities Management Services Procurement in Public Buildings in Abuja-Nigeria Sani Momoh, Jennifer Ayegba, Luqman Oyewobi, Calistus Ayegba, Abdulquadri Bilau & Richard Jimoh Hydropower Sustainability Assessment Protocol (HSAP) Implementation in Indonesia: A mini-review Novi Andriany Teguh & Ainul Firdatun Nisaa Weighting The Fire Protection Systems Technical Requirements to Determine Flats Reliability Against Fire Hazards Aris Aminulwahyu, I Putu Artama Wiguna & Tri Joko Wahyu Adi Purabaya Bus Station Service Performance in New Adaptation Period Putu Cinthya Pratiwi Kardita, Achmad Wicaksono & M. Ruslin Anwar Modeling and Optimization of the Compressive Strength of High Volume Fly Ash ECC with Low Modulus PVA Fiber Using Response Surface Methodology (RSM) Isyaka Abdulkadir & Bashar S. Mohammed Implementation of Risk Management in Property Projects I Wayan Muka & Agung Wibowo A New Approach to Estimate the Potential Assets Loss due to Dam-Break Event in Indonesia Farrell Wiguna, Doddi Yudianto, Bobby Minola Ginting & Albert Wicaksono